In-depth study of the nutritional composition, phytochemicals, antioxidant activity, molecular docking interactions, and toxicological evaluation of Abies marocana Trab. woody biomass - Zirari, Malak; Aouji, Marouane; Baghdad, Wissal; Er-rajy, Mohammed; Imtara, Hamada; Abujaber, Feras; Elharrati, Otmane; Noman, Omar M.; Tarayrah, Mahmoud; Hmouni, Driss; Mejdoub, Nouredine El (Frontiers in Sustainable Food Systems, 2025)
IntroductionMorocco is renowned for its rich plant biodiversity, although many plants are underutilized. Consequently, the present study was conducted to assess the nutritional composition, bioactive constituents, antioxidant properties, and acute oral toxicity of Abies marocana's woody biomass.MethodsThe nutritional value of the twigs and cones was determined using the AOAC method, while mineral components were examined through ICP-OES. To search for phytochemicals in the methanolic extracts, a number of established techniques were applied, and evaluate their antioxidant activity, while the volatile content was determined using the GC-MS method. The acute oral toxicity test was carried out following the guidelines of OECD 423.Results and discussionProximate analysis revealed a variety of components in different parts, including moisture, ash, fiber, protein, carbohydrates, and fat. Cones and twigs were found to be rich in mineral elements, as well as phenols, flavonoids, tannins, and phytosterols. Chromatographic analysis identified linoleic acid as the main component in twig extract and 2-Bornanone as the primary constituent in cone extract. The methanolic extracts of A. marocana displayed strong antioxidant properties through notable DPPH scavenging activity, with no mortality observed in rats even at doses exceeding 1,000 mg.kg−1, indicating potential for medicinal, cosmetic, or dietary uses. A molecular docking study of the five main compounds of both plants showed that they aligned and interacted with the binding sites of selected proteins, demonstrating significant antioxidant activity.